Estresse por alumínio em cultivares de cana-de-açúcar: crescimento radicular e atividade de enzimas antioxidantes - Pimenta, Lucas Smith (Universidade Federal de São Carlos, 2017)
Sugarcane (Saccharum spp.) is the most important crop for the economy of more than a hundred tropical and subtropical countries, accounting for 70% of the sugar and 40% of the ethanol production worldwide. Aluminium toxicity (Al3+) on acidic soils is the second major abiotic stress, after drought, affecting crop’s productivity. Al3+ directly limits sugarcane productivity through the inhibition of root development, promoting yet the unbalance between the production and elimination of reactive oxygen species (ROS). The use of liming for correcting soil acidity is an expensive and temporary solution, being the adoption of cultivars tolerant to Al3+ a more sustainable practice in the long term. Several grass species have Al3+ tolerant cultivars, which have been studied and successfully used to obtain more productive genotypes. The present study aimed to evaluate the tolerance to Al3+ in a group of sugarcane cultivars, through root growth and antioxidant enzymes activities (APX, CAT and SOD). A series of hydroponics experiments were conducted to define Al3+ activity and the minimum acclimation and exposure periods required to verify the behavior of the cultivars. The proposed system, with seven days of acclimatization and three days of exposure to 143 μM Al3+, was adequate to study the cultivars. In the last experiments conducted, nine cultivars were evaluated in the absence (0 μM Al3+) or presence of 143 μM Al3+, which were separated into two groups, based on the relative root growth (RRG). In the control experiment (0 μM Al3+) RRG showed no significant correlation with the activity of any of the antioxidant enzymes studied. In contrast, in the Al treatment experiment (143 μM Al3+), significant correlations (p≤0.05) were obtained between RRG and the enzymes CAT and SOD. The results indicate a possible role of these enzymes in the maintenance of the oxidative status and root growth in sugarcane plants exposed to Al3+.
Aluminium stress in sugarcane cultivars: root growth and activity of antioxidant enzymes
Keywords: Alumínio tóxico; EROs; Alumínio; Enzimas antioxidantes; Toxic aluminium; ROS; Aluminium; Antioxidant enzymes; CIENCIAS AGRARIAS